Strong, Ductile, and Waterproof Cellulose Nanofibril Composite Films with Colloidal Lignin Particles - Farooq, Muhammad; Zou, Tao; Riviere, Guillaume; Sipponen, Mika H; Österberg, Monika (Biomacromolecules, 2019)
Brittleness has hindered commercialization of cellulose nanofibril (CNF) films. The use of synthetic polymers and plasticizers is a known detour that impairs biodegradability and carbon footprint of the product. Herein, we utilize a variety of softwood Kraft lignin morphologies to obtain strong and ductile CNF nanocomposite films. An optimum 10 wt % content of colloidal lignin particles (CLPs) produced films with nearly double the toughness compared to a CNF film without lignin. CLPs rendered the films waterproof, provided antioxidant activity and UV-shielding with better visible light transmittance than obtained with irregular lignin aggregates. We conclude based on electron microscopy, dynamic water sorption analysis, and tp-DSC that homogeneously distributed CLPs act as ball bearing lubricating and stress transferring agents in the CNF matrix. Overall, our results open new avenues for the utilization of lignin nanoparticles in biopolymer composites equipped with versatile functionalities for applications in food packaging, water purification, and biomedicine.